Recycled Material to Promote Motivation and Interaction in Teaching - Atrisco, Sandra; Charco, Dalia (CIEX JOURNAL, 2020)
All the students’ necessities in learning a foreign language and the continuous evolution of education has brought to light great teaching strategies such as using handmade recycled materials. This workshop seeks to promote innovative strategies for teaching English at basic levels, particularly, with primary students which may also influence their motivation. For such a purpose, students develop their own didactic materials, which naturally increases student participation as well as teachers’ motivation.